A Comparative Study of the Relationship Between Rights and Good in Rawlsian Perspective on the Protests Against the Murder of George Floyd (2020) and the Protests Against the Palestinian Genocide (2024) in the United States - Maysam Baharloo; Mohamed Sadiq Nosratpanah (رهیافتهای سیاسی و بین المللی)
Extended AbstractIntroduction and Objectives: This article offers a comparative study of the relationship between the concepts of the “right” and the “good” in John Rawls’s political philosophy, with a focus on their implications for domestic politics in the United States. The main objective is to examine how these two normative concepts played out during two major instances of civil protest: the protests following the killing of George Floyd in 2020, and the protests against the genocide in Palestine in 2024. John Rawls, emphasizing the priority of the right over the good, conceives political philosophy as a framework for achieving fundamental agreement and resolving social conflicts in a pluralistic society. In light of this, the article explores how the interplay between the concepts of right and good influenced the policy responses and ideological orientations of the U.S. political elite—especially within the two dominant parties—during these protest movements.Methods: This study employs a method of philosophical analysis. In the first stage, the Rawlsian concepts of right and good are identified and elaborated, primarily as presented in A Theory of Justice. These concepts are then compared with Rawls’s later works and with the ideas of other political philosophers, especially Immanuel Kant, in order to clarify their role within political theory. Subsequently, Rawls’s position is contrasted with alternative frameworks—particularly utilitarianism—to highlight the distinction between emphasizing the priority of right versus that of good. Finally, through a comparative evaluation, the study analyzes how these philosophical distinctions influenced U.S. political and social reactions to the crises in question.Results and Discussion: The findings indicate that the Democratic Party has generally prioritized the protection of individual rights and liberties, whereas the Republican Party tends to emphasize the protection of the public good—often framed in terms of public security, national pride, Christian values, and similar ideals. Thus, during the George Floyd protests, the Trump administration—under pressure from Democratic discourse and public mobilization—partially aligned with Rawlsian principles by affirming certain rights-based claims. In contrast, during the 2024 protests against the genocide in Palestine, both major parties, including the Biden administration, prioritized conceptions of the public good (e.g., foreign policy interests, national security, and strategic alliances) over the individual rights of protestors and marginalized groups. Conclusions: This analysis suggests that the departure from Rawls’s principle of the priority of the right over the good—particularly evident during the Palestinian protests—stems from the concentration of wealth and influence within a semi-hidden oligarchic structure. This system justifies itself through an appeal to the protection of private property rights. One striking example is the role of lobbying organizations such as the American Israel Public Affairs Committee (AIPAC), which, by financing electoral campaigns, has effectively constrained democratic responsiveness and subordinated fundamental rights to vested interests. This issue also touches on a broader critique of liberal neutrality. As conservative philosopher John Kekes argues in Against Liberalism, the liberal state cannot remain neutral with regard to the values it seeks to uphold. In pluralistic societies, groups may emerge that reject liberal rights altogether—and, through political mobilization, may gain significant influence. This calls into question whether a liberal state can consistently maintain neutrality while preserving its foundational principles.